The prolonged movement of non-performing assets in both Indian public and private sector banks: A pragmatic assessment. Issue 7 (3rd October 2022) - Kumar, Arya; Mohanty, Debashisa; Mishra, Apoorva; Chaudhary, Niyati
Abstract: The failure of the financial system pulls down the business and country's economy when it is experienced in the case of banks. A good performance of the banking system upholds the nation's goodwill and economy. Banking activities indulge in lending activities, but the challenge of credit risk sustains with the banks unwantedly which leads to the rising of non-performing assets (NPA). The present study encounters the responses by the bankers of both private and public banks regarding the sky touching rise of NPAs to highlight the significant responsibility for the unwanted rise and identify the similarity of responses by both types of banks. The consequence is significantly true for both types of banks as they agree to the responses for the NPAs that are slowly rising and further, the study confirms that the major stake for NPAs is due to the lending of funds to agricultural and industrial sectors and with the highest credit burden owing by the governments' organization.